Non-response to psychotherapy for borderline personality disorder: A systematic review. (July 2022) - Woodbridge, Jane; Townsend, Michelle; Reis, Samantha; Singh, Saniya; Grenyer, Brin FS
Highlight: This is the first systematic review to investigate non-response to psychotherapy for borderline personality disorder. Background: Psychotherapy is the recommended treatment for borderline personality disorder. While systematic reviews have demonstrated the effectiveness of psychotherapy for borderline personality disorder, effect sizes remain small and influenced by bias. Furthermore, the proportion of people who do not respond to treatment is seldom reported or analysed. Objective: To obtain an informed estimate of the proportion of people who do not respond to psychotherapy for borderline personality disorder. Methods: Systematic searches of five databases, PubMed, Web of Science, Scopus, PsycINFO and the Cochrane Library, occurred in November 2020. Inclusion criteria: participants diagnosed with borderline personality disorder, treated with psychotherapy and data reporting either (a) the proportion of the sample that experienced 'reliable change' or (b) the percentage of sample that no longer met criteria for borderline personality disorder at conclusion of therapy. Exclusion criteria: studies published prior to 1980 or not in English. Of the 19, 517 studies identified, 28 met inclusion criteria. Results: Twenty-eight studies were included in the review comprising a total of 2436 participants. Average treatment duration was 11 months using well-known evidence-based approaches. Approximately half did not respond to treatment; M = 48.80% (SD = 22.77). Limitations: Data regarding within sample variability and non-response are seldom reported. Methods of reporting data on dosage and comorbidities were highly divergent which precluded the ability to conduct predictive analyses. Other limitations include lack of sensitivity analysis, and studies published in English only. Conclusion: Results of this review suggest that a large proportion of people are not responding to psychotherapy for borderline personality disorder and that factors relating to non-response are both elusive and inconsistently reported. Novel, tailored or enhanced interventions are needed to improve outcomes for individuals not responding to current established treatments.